2021
DOI: 10.1111/sjop.12763
|View full text |Cite
|
Sign up to set email alerts
|

Perception of workplace social‐sexual behavior as sexual harassment post #MeToo in Scandinavia

Abstract: In this study we examined how people perceive social‐sexual behavior of women and men, and how these perceptions were associated with beliefs about the outcomes of the #MeToo movement, sexism, traditional values, and gender equality. In addition, we examined the effect of having experienced sexual harassment on such perceptions. Analyses were performed on a Norwegian snowball social media sample covering 321 women and 168 men, aged 18–59 (M = 33.1). Outcome variables covered perceptions of scenarios that descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
1
9
1
Order By: Relevance
“…Brown et al, 2017). As a result, men become desensitised to sexual harassment because conversations of a sexual nature are customary (Kessler et al, 2021). Akin to this, distinguishing between what is harmless sexual banter and what is sexual harassment is challenging, making it hard to recognise (Page et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Brown et al, 2017). As a result, men become desensitised to sexual harassment because conversations of a sexual nature are customary (Kessler et al, 2021). Akin to this, distinguishing between what is harmless sexual banter and what is sexual harassment is challenging, making it hard to recognise (Page et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly for the present contribution, Moscatelli et al [19] found that higher hostile sexism toward women predicted women's higher skepticism toward the allegations made by the victims of the so-called "Weinstein scandal" and more negative views of the #MeToo campaign. Similarly, hostile sexism was associated with more negative beliefs concerning the outcomes of the movement, which in turn were associated with a higher tendency to consider social-sexual behaviors as sexual harassment [6].…”
Section: Ambivalence Toward Women and Men As An Antecedent Of Attitud...mentioning
confidence: 96%
“…The #MeToo movement also affected the extent to which people considered socialsexual behaviors in the workplace, such as sexist jokes, repeated invitations to date following a polite rejection, or hugs lasting "a little too long" as sexual harassment [6,30]. Through a four-wave longitudinal study, Szekeresa et al [7] demonstrated that lay people's dismissal of sexual assault decreased following the campaign.…”
Section: The #Metoo Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017 October, American female artist Alyssa Milano poll out a scandal about Allegations of sexual abuse against several women by the Us producer Harvey Weinstein. She recommends that all women who have been sexually assaulted are urged to come forward with their stories and tag #METOO on social media to raise awareness [5].METOO movement is so important because it is the first time that This is the first such large woman's campaign against sexual harassment [1]. Alibaba, an Internet company, was exposed to a sex scandal on August 6, 2021.…”
Section: Introductionmentioning
confidence: 99%